Sustainable business models and eco-innovation: A life cycle assessment - Barbieri, Renata; Santos, David Ferreira Lopes [UNESP] (Elsevier, 2020)
Eco-innovative business models are prominent elements of the development of sustainable production and consumption systems in organizations of all sizes, especially for small and medium enterprises, where a key challenge is to direct eco-innovation strategies toward the goals of their business model. Therefore, using product life cycle assessment, this research analyzed the alignment between the sustainable business model and the eco-innovative strategies of a Brazilian company in the veterinary homeopathy pharmaceutical industry. Disregarding the controversial discussion about homeopathy, this activity has shown significant growth, having a representative economic importance in the animal protein production chain. The research adopted a case study method for one of Brazil's leading companies in this activity. Data were collected through interviews, process analysis and company records. The results were built through quantitative and qualitative techniques that demonstrated that the eco-innovations developed by the company are directed toward the creation of new production methods and, above all, new products. The management model was framed in the “adopt a management role” archetype, in accordance with the literature. It was found that eco-innovation strategies are important for the development of the company's business model and that this alignment is possible only when there is a management system and investments in the company's ability to eco-innovate in product, process and organizational structure.
Keywords: Agribusiness; Organizational innovation; Sustainable development indicators; Veterinary medicine